EVALUATING THE THERAPEUTIC EFFICACY OF SHOCKWAVE THERAPY IN THE TREATMENT OF PLANTAR FASCIITIS AT HAI PHONG UNIVERSITY OF MEDICINE HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the clinical outcomes of shockwave therapy in the treatment of plantar fasciitis at the Rehabilitation Department of Hai Phong University of Medicine Hospital.Methods: A cross-sectional descriptive study was conducted on 36 patients meeting the inclusion criteria at the Rehabilitation Department of Hai Phong University of Medicine Hospital from January 2025 to October 2025.Results: Extracorporeal shockwave therapy demonstrated superior efficacy after 4 weeks of treatment for plantar fasciitis. Pain levels, measured by the Visual Analog Scale (VAS), decreased significantly, with no patients remaining in the severe pain category. Notable improvements were observed in the Heel Tenderness Index (HTI) and plantar fascia thickness as measured by ultrasound. According to the American Orthopaedic Foot and Ankle Society (AOFAS) score, 100% of patients achieved "Good" or "Excellent" outcomes after 4 weeks, with the "Excellent" rate accounting for the majority (86.1%).Conclusion: Extracorporeal shockwave therapy is highly effective and safe for treating plantar fasciitis. It provides significant therapeutic benefits without altering the anatomical axis of the foot.
Keywords: Plantar fasciitis, shockwave therapy, pain level, heel tenderness, plantar fascia thickness.